A feastful of islands ; Prisoners ; Monique's new voice [videorecording] - Canlas, Ruben, Jr.; Cantada, Candy; Lazaro, Cheche; Ortigas, Marga (Quezon City Probe Productions, 1995)
Investigates the Spratly Islands conflict; the forty eight Muntinlupa prisoners in their forty one days hunger strike calling themselves political prisoners and an interview with singer Monique Wilson.
A fistful of islands (18 min.) -- Prisoners (12 min.) -- Monique's voice (12 min.)
VHS.
Credits : Reporters, Luchi Cruz-Valdez, Marga Ortigas, Cheche Lazaro.
Keywords: Wilson, Monique -- Interviews; Political prisoners -- Philippines -- Muntinlupa; Prisoners -- Philippines -- Muntinlupa; Spratly Islands (Philippines) -- International status; Kalayaan Islands (Philippines) -- International status